Antibacterial Activity Test of Gotu Kola Leaf Extract (Centella asiatica) Against Staphylococcus aureus Bacteria Isolated from Wounds of Diabetes Mellitus Patients - Fioni; Debby Heldayani; Gilbert Lister; Andika Zayani Tambunan (Jurnal Penelitian Pendidikan IPA, 2023)
Staphylococcus aureus, a gram-positive bacterium, is the causative agent of diabetic foot. Traditional medicine using plants needs much further research, especially for wound healing in diabetes mellitus patients. This study is an experimental laboratory investigation on the efficacy of Gotu kola (Centella asiatica) leaf extract against wound-isolated Staphylococcus aureus. Gotu kola leaf extract (12.5%, 25%, 50%, 75%, and 100%), cefixime suspension (positive control), and sterile distilled water were tested. The results of the research showed the formation of an inhibitory zone from testing Gotu kola leaf extract against Staphylococcus aureus bacteria, where the average inhibitory zone was at concentrations of 12.5% (7.2 mm), 25% (11 mm), 50% (13.7 mm), 75% (14 .3 mm), and 100% (19.5 mm). The higher the concentration used, the larger the inhibition zone formed. Research shows that Gotu kola leaves' active substances inhibit energy formation, nucleic acid formation, cell membrane permeability, structure and function, and membrane protein lysis and damage.